2016
DOI: 10.1177/0004563216638108
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA-135a-5p as an auxiliary diagnostic biomarker for colorectal cancer

Abstract: Objective The purpose of this study was to explore serum miR-135a-5p expression in colorectal cancer and examine the potential usefulness of this molecule as a biomarker for diagnosis in colorectal cancer. Methods Serum samples were collected from 60 patients with primary colorectal cancer, 40 patients with colorectal polyps and 50 healthy controls. Serum miR-135a-5p expression levels were detected by reverse transcription quantitative real-time quantitative polymerase chain reaction. Serum carcinoembryonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
(24 reference statements)
2
17
0
2
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Recent studies revealed that miRNAs are stably present in serum. The expression patterns of serum miRNAs are closely correlated with progression and prognosis in a variety of human tumors, including lung cancer, colorectal cancer, prostate cancer, gastric cancer, osteosarcoma, and so on 18-24. Circulating miRNAs could be considered as a novel promising diagnostic and prognostic biomarker for cancer screening because: (ⅰ) serum miRNAs are readily detectable by RT-qPCR, a technique that widely used in clinical laboratories; (ⅱ) blood-based biomarkers are minimally invasive for the screening of high-risk subjects and early diagnosis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, miRNA-135a showed a inhibitive role during the migration and invasion of lung cancer cells, due to targeting a transcription factor [19] . However, the functions and mechanisms of miRNA-135a during tumors are largely unknown [20][21][22][23] . Recent studies have demonstrated that miRNA-135a is up-regulated in CC cell lines SW480 and SW620, while in our study, the expression levels of miRNA-135a were significantly increased in CC tissues, which was in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 99%